A Community Initiative at Toli-toli Village, Regency of Konawe, Province of Southeast Sulawesi - Yasir Haya, La Ode M. (Journal of Indonesian Coral Reefs, 2012)
Giant clam (Tridacna sp) are one of the endangered species listed on the Red List of Threatened Species by the IUCN, which is grouped at CITES. In Indonesia, efforts to protect it have not beeneffective due to a lack of supervision and law enforcement support. The local community of Toli-toli in the Province of Southeast Sulawesi, has made efforts to save the species from exploitation and poaching. This effort was supported by the village head and the local community by the establishment the Giant Clam of Marine Protected Area (MPA). Data was collected by in-depth interviews and focus group discussions. The sampling consisted of the village head, community leaders, fishermen and clam conservation groups. Data analyses were performed using qualitative descriptive methods â Analysis Individual Interest Matrix (AIIM) and Analysis Hierarchy Process (AHP) - to determine management priorities to protect the clams. The results show that through community-based management, a local village community accepts the establishment of the MPA. The total area reserved for this MPA was 60 hectares, spread over 4 sites of clam translocations. MPA management would have 5 priorities: formal legalization of MPA (0.281), zoning areas (0.253), management institution (0.181), community-based ecotourism (0.175), and development of alternative livelihoods (0.110). This model is an alternative one in the effort to protect clam species and to improve the coastal community welfare around the MPA sites.Â